Caring for health : history and diversity - Webster, Charles, 1936- (Health and disease series, 1993)
A study of the historical development of health services, institutions and occupations in health care, and wider public health policies, from 1500 to the present day. Focusing primarily on the UK, it pays particular attention to the relationship between formal and lay health care